2014
DOI: 10.1038/aps.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol effectively attenuates α-naphthyl-isothiocyanate-induced acute cholestasis and liver injury through choleretic and anti-inflammatory mechanisms

Abstract: Aim: α-Naphthylisothiocyanate (ANIT) is a well-characterized cholestatic agent for rats. The aim of this study was to examine whether resveratrol could attenuate ANIT-induced acute cholestasis and liver injury in rats. Methods: SD rats were treated with resveratrol (15 or 30 mg/kg, ip) or a positive control drug ursodeoxycholic acid (100 mg/kg, po) for 5 consecutive days followed by a single dose of ANIT (60 mg/kg, po). Bile flow, and serum biochemical markers and bile constituents were measured 48 h after ANI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 36 publications
10
37
0
1
Order By: Relevance
“…The modulation of pro-inflammatory responses plays a critical role in cholestatic liver injury [33] . The present study demonstrated that hepatic MPO activity was significantly increased after ANIT exposure, which is consistent with results from a previous study [34] . However, oral sweroside administration alleviated the increase in hepatic MPO activity after ANIT treatment, which contributed to the inhibition of neutrophil infiltration into liver tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The modulation of pro-inflammatory responses plays a critical role in cholestatic liver injury [33] . The present study demonstrated that hepatic MPO activity was significantly increased after ANIT exposure, which is consistent with results from a previous study [34] . However, oral sweroside administration alleviated the increase in hepatic MPO activity after ANIT treatment, which contributed to the inhibition of neutrophil infiltration into liver tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have demonstrated that bile acid synthesis may be inhibited during liver damage [33,34] . The present study demonstrated that sweroside significantly attenuated the down-regulation of Cyp7a1, Cyp8b1, and Hsd3b7, which is consistent with results from previous reports [14,17] .…”
Section: Discussionmentioning
confidence: 98%
“…Nrf2 can regulate the expression and activation of variety of enzymes that counteract oxidative stress and promote cell survival [30,31]. In addition, studies have shown that the activation of Nrf2 can safeguard against cholestasis caused by bile duct ligation and alphanaphthyl isocyanate models via the induction of many anti-oxidative genes [5,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Our data may provide an alternative explanation for this observation: the protective role of TER may arise from its inhibition of NTCP function, which leads to less bile acid accumulation in hepatocytes and less apoptosis. However, from another perspective, down-regulation of NTCP and disturbance of bile acid circulation may lead to liver toxicity over the long term [32][33][34] . In fact, the elimination half-life of TER is approximately 2 weeks, which is thought to result from a combination of extremely low hepatic clearance and enterohepatic recycling [27,35] .…”
Section: Discussionmentioning
confidence: 99%